2010
DOI: 10.1007/s00259-010-1570-6
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluorodeoxyglucose positron emission tomography and computed tomography in anaplastic thyroid cancer

Abstract: FDG PET/CT appears to be the reference imaging modality for ATC at initial staging and seems promising in the early evaluation of treatment response and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 37 publications
0
45
0
3
Order By: Relevance
“…Death is more often related to distant metastases than to local disease progression. Poisson et al (54) observed that FDG-PET/CT was the reference imaging modality for ATC at initial staging because it was more effective than CT was in detecting cervical and mediastinal lymph nodes. FDG-PET/CT was more sensitive than bone scintigraphy; the volume of FDG uptake (O300 ml) and the intensity of FDG uptake (SUVmax R18) were significant prognostic factors for survival; FDG-PET/CT was also more efficient in the early assessment of tumor volume and in the response to treatment than CT was.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Death is more often related to distant metastases than to local disease progression. Poisson et al (54) observed that FDG-PET/CT was the reference imaging modality for ATC at initial staging because it was more effective than CT was in detecting cervical and mediastinal lymph nodes. FDG-PET/CT was more sensitive than bone scintigraphy; the volume of FDG uptake (O300 ml) and the intensity of FDG uptake (SUVmax R18) were significant prognostic factors for survival; FDG-PET/CT was also more efficient in the early assessment of tumor volume and in the response to treatment than CT was.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…As a result of aggressive tumor behavior and ineffective therapeutic efficacy, patients do poorly (Besic & Gazic 2013). Positron emission tomography (PET)/computed tomography (CT) is the primary imaging modality for ATC at initial staging and has utility in the early evaluation of treatment response and follow-up (Poisson et al 2010). Distant metastases, extensive local infiltration, and regional lymph node metastases have been found at autopsy in 91, 76, and 51% of cases respectively.…”
Section: Dear Editormentioning
confidence: 99%
“…Furthermore FDG PET/CT seems promising in the early evaluation of treatment response and follow-up [28].…”
Section: Role Of Imagingmentioning
confidence: 99%
“…PET may therefore improve disease detection and impact significantly on the management of patients with ATC relative to other imaging modalities [27,28].…”
Section: Role Of Imagingmentioning
confidence: 99%
See 1 more Smart Citation